Bush at War - Woodward, Bob (New York Simon & Schuster, 2002)
Award-winning author and journalist Bob Woodward turns his attention to the presidency of George W. Bush. Before the acts of terrorism on 11 September, George W. Bush's presidency had been beset by numerous problems. Not only was it in many peoples eyes invalid, very few people took him seriously as a world statesman.
Include Illustration and Index
Keywords: Bush, George W. (George Walker), 1946- -- War on Terrorism -- Military leadership